Comorbidity of Pain and Depression in a Lumbar Disc Herniation Model: Biochemical Alterations and the Effects of Fluoxetine - Cai, Lun; He, Qianchao; Lu, Yongjing; Hu, Yuying; Chen, Wei; Wei, Liping; Hu, Yueqiang (Frontiers in Neurology, 2019)
LDH model shows a behavioural and biochemical alterations that in accordance with the characteristic of commorbity of pain and depression and FLX improve depressive behavior and alleviate pain through increased 5-HT concentration and inhibited TNF-α mRNA expression in this model.